Concept of Diet in Traditional Yoga Texts: A Review - Chhetri, Archana; Sharma, Romesh Kumar; Chetry, Dipak (International Research Journal of Ayurveda & Yoga, 2024)
The concept of yogic diet is one of the fundamental principles provided by yoga texts for the attainment of well-being. Therefore, the goal of this review was to systematically examine the specificities of yogic diet based on specific verses and how it is classified in several important ancient yogic texts, including the Hatha Yoga Pradipika (HYP), Gheranda Samhita (GS) and Bhagavad Gita (BG). In the current analysis of the classic texts, Hatha Yoga Pradipika, Gheranda Samhita and Bhagavad Gita shows that diet is discussed in eight, seventeen and six verses of these classical yogic texts respectively. The Hatha Yoga Pradipika (HYP) and Gheranda Samhita (GS) mentioned three different food categories: (1) Mitahara, (2) Pathya Ahara, and (3) Apathya Ahara. The Bhagavad Gita (BG) divided the food into three categories: (1) Swattik Ahara, (2) Rajaswik Ahara, and (3) Tamasik Ahara. In conclusion, the overall findings revealed the diverse and distinct perspective on diet in each yoga texts. Future researchers will be able to look at and compare yogic diet with modern dietary classifications and their nutritional properties. By pointing out shortcomings in the current evaluation, researchers can also use resources to conduct more thorough research on compound diets for the next study.